Epigenetic reprogramming and re-differentiation of a Ewing sarcoma cell line - Moore, Joseph B.; Loeb, David M.; Hong, Kyung U.; Sorensen, Poul H.; Triche, Timothy J.; Lee, David W.; Barbato, Michael I.; Arceci, Robert J. (Frontiers in Cell and Developmental Biology, 2015)
Developmental reprogramming techniques have been used to generate induced pluripotent stem (iPS) cells from both normal and malignant cells. The derivation of iPS cells from cancer has the potential to provide a unique scientific tool to overcome challenges associated with the establishment of cell lines from primary patient samples and a readily expandable source of cells that may be used to model the initial disease. In the current study we developmentally reprogrammed a metastatic Ewing sarcoma (EWS) cell line to a meta-stable embryonic stem (ES)-like state sharing molecular and phenotypic features with previously established ES and iPS cell lines. EWS-iPS cells exhibited a pronounced drug resistant phenotype despite persistent expression of the oncogenic EWS-FLI1 fusion transcript. This included resistance to compounds that specifically target downstream effector pathways of EWS-FLI1, such as MAPK/ERK and PI3K/AKT, which play an important role in EWS pathogenesis. EWS-iPS cells displayed tumor initiation abilities in vivo and formed tumors exhibiting characteristic Ewing histopathology. In parallel, EWS-iPS cells re-differentiated in vitro recovered sensitivity to molecularly targeted chemotherapeutic agents, which reiterated pathophysiological features of the cells from which they were derived. These data suggest that EWS-iPS cells may provide an expandable disease model that could be used to investigate processes modulating oncogenesis, metastasis, and chemotherapeutic resistance in EWS.